Abdominal Cutaneous Nerve Entrapment Syndrome, Case Report and Diagnostic Evaluation - Guedes-Correa, Jose Fernando; Bulhões, Stephanie Oliveira Fernandes de (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2019)
Abdominal cutaneous nerve entrapment is a rarely diagnosed condition that leads to intense neuropathic pain in the anterolateral wall of the abdomen. Generally, it is triggered by some factor implied in the increase of the pressure on the nerve in its passage by the abdominal wall. Its most important differential diagnosis is pain of visceral origin.We present a case in which the clinical findings confirmed on ultrasound and other imaging tests established the diagnosis and in which the noninvasive treatment was effective.
Keywords: nerve compression syndrome; ultrasonography; diagnostic imaging